Tuning Structural and Optical Properties of WO3 NPs Thin Films by the Fluency of Laser Pulses - Ali Jaafar Hwaidi; Prof. Dr. Nadheer Jassim Mohammed (Al-Mustansiriyah Journal of Science, 2022)
In this paper, tungsten oxide thin films were successfully synthesized by the laser pulse deposition (PLD) method using a pulsed laser (ND-YAG) and wavelength (1064 nm) on a glass substrate at different laser fluencies. The effect of increasing laser fluency, on the optical and structural properties of WO3 nanoparticle thin films, was investigated by UV-Visible spectrophotometer, X-Ray diffraction (XRD), atomic force microscope (AFM) and Scanning Electron Microscope (SEM). X-Ray measurements for all samples of WO3 NPs thin films have shown that by increasing the laser fluencies from 5.175 to 6.369 J/cm2, the intensity of the (2 01) diffraction peak increases due to the film continuing to grow with increased crystallization.